Identification of new F8 deep intronic variations in patients with haemophilia A. Issue 5 (18th August 2020) - Dericquebourg, Amy; Jourdy, Yohann; Fretigny, Mathilde; Lienhart, Anne; Claeyssens, Ségolène; Ternisien, Catherine; Boisseau, Pierre; Rohrlich, Pierre‐Simon; Négrier, Claude; Vinciguerra, Christine
Abstract: Introduction: With current molecular diagnosis, about 1 to 5% of haemophilia A (HA) patients remain genetically unresolved. In these cases, deep intronic variation or structural variation disrupting the F8 gene could be causal. Aim: To identify the causal variation in four genetically unresolved mild‐to‐severe HA patients using an F8 mRNA analysis approach. Methods: Ectopic F8 mRNA analysis was performed in four unrelated HA patients. An in vitro minigene assay was performed in order to confirm the deleterious splicing impact of each variation identified. Results: In all probands, mRNA analysis revealed an aberrant splicing pattern, and sequencing of the corresponding intronic region found a deep intronic substitution. Two of these were new variations: c.2113+601G>A and c.1443+602A>G, while the c.143+1567A>G, found in two patients, has previously been reported. The c.1443+602A>G and the c.143+1567A>G variants both led to the creation of a de novo acceptor or donor splice site, respectively. Moreover, the c.143+1567A>G was found in 3/6 patients with genetically unresolved moderate HA registered in our laboratory. Haplotype analysis performed in all patients carrying the c.143+1567A>G variation suggests that this variation could be a recurrent variation. The c.2113+601G>A led to the exonization of a 122‐bp antisense AluY element by increasing the strength of a pre‐existing cryptic 5' splice site. For each point variation, in vitro splicing analysis confirmed its deleterious impact on splicing of the F8 transcript. Conclusion: We identified three deep intronic variations, leading to an aberrant mRNA splicing process as HA causing variation.